Sheep cheese naturally enriched in α-linolenic, conjugated linoleic and vaccenic acids improves the lipid profile and reduces anandamide in the plasma of hypercholesterolaemic subjects - Pintus, Stefano; Murru, Elisabetta; Carta, Gianfranca; Cordeddu, Lina; Batetta, Barbara; Accossu, Simonetta; Pistis, Danila; Uda, Sabrina; Elena Ghiani, Maria; Mele, Marcello; Secchiari, Pierlorenzo; Almerighi, Guido; et al. (British journal of nutrition, 2013)
Intake of dairy fat has long been considered as a risk factor for CVD. Pasture and dietary lipid supplementation have been reported to be reliable strategies in ruminant nutrition, in order to increase the content of α-linolenic acid (ALA), conjugated linoleic acid (CLA) and vaccenic acid (VA), and decrease SFA in milk fat. In the present study, we aimed at verifying whether consumption of a sheep cheese, naturally enriched in ALA, CLA and VA, would modify the plasma lipid and endocannabinoid profiles in mildly hypercholesterolaemic subjects. A total of forty-two adult volunteers (nineteen males and twenty-three females) with diagnosed mildly hypercholesterolaemia (total cholesterol 5·68–7·49 mmol/l) were randomly assigned to eat 90 g/d of a control or enriched cheese for 3 weeks, with a cross-over after 3 weeks of washout. Plasma lipids, endocannabinoids, adipokines and inflammatory markers were measured. The intake of enriched cheese significantly increased the plasma concentrations of CLA, VA, the n-3 fatty acids ALA and EPA, and more remarkably decreased that of the endocannabinoid anandamide. LDL-cholesterol decreased significantly (7 %). No changes were detected in the levels of inflammatory markers; however, a significant correlation was found between the plasma levels of anandamide and leptin. The control cheese modified none of the parameters measured. The results obtained do not support the view that intake of dairy fat is detrimental to hypercholesterolaemic subjects. Indeed, they show that a naturally enriched cheese possesses beneficial properties, since it ameliorates the plasma lipid profile, and more remarkably reduces endocannabinoid biosynthesis.